Similitudo ex argilla. Invenzione della coroplastica e dimensione magica in un racconto di Plinio - Giuman, Marco (O T I V M, 2025)
The document examines Pliny’s aition on the invention of coroplastic art in the story of Butades of Sicyon and his daughter (Naturalis Historia XXXV, 151), proposing an interpretation that analyses the overlap between technical dimension and magical-symbolic meaning. Located at the conclusion of Pliny’s discussion of painting, this passage establishes a functional link between the practice of circumductio umbrae and the origins of the figurative arts, framing the tracing of shadows as the archetype of both painting and clay modelling. The study focuses on the gesture of the daughter, whose act of love – motivated by the departure of her lover – takes the form of a magical ritual in which a simulacrum transforms absence into permanence.